CSR implementation of palm oil plantations through the integrated farming system program in empowering local farmer groups - Arhian Veronika Suryajuanti; Murti B S Sigit Heru; Baliarti Endang (BIO Web of Conferences, 2023)
The concept of corporate social responsibility (CSR) emerged in response to the development of sustainable corporations that prioritize sustainable development practices. The Sintang District Government's economic improvement program aims to boost community income by developing the UMKM sector (Micro, Small, Medium Enterprises). To integrate palm oil plantations with livestock, the local government initiated this effort. The research method used is a descriptive study - with qualitative data types through data collection techniques conducted utilizing interviews, observations, and literature studies. The study found that the application of CSR in Indonesia does not fully align with the legal definition of CSR. The implementation of CSR is primarily focused on short-term aid provision to local communities. The integration of livestock farms has not been implemented by all plantation companies, and the ones that do exist are suboptimal. Even though Sintang Regency cannot meet the local beef needs, farmers are only capable of meeting 20-30% of the annual demand. Consequently, to meet the demand, the government must purchase livestock from outside Sintang district and even from outside the province of West Kalimantan.